Evolutionary Psychology: A Fresh Perspective for Understanding and Changing Problematic Behavior. (17th January 2013) - Tybur, Joshua M.; Griskevicius, Vladas
<x xml:space="preserve">Abstract</x> From rising obesity and soaring health care costs to escalating violence and environmental degradation, contemporary society faces many challenges. Are there policies that are naturally effective in changing the behaviors that produce these problems? In this article, the authors examine some of the roots of socially problematic behavior by taking an evolutionary perspective that considers human nature. They review four insights that an evolutionary approach provides into human behavior. Then they discuss how a deeper understanding of the ancestral roots of modern behavior can provide a fresh perspective for policy makers and public administrators while also providing fertile ground for novel research and applications for altering behavior. The central takeaway is that optimal strategies for changing problematic behaviors require harnessing our deep‐seated ancestral nature rather than ignoring it or working against it.